Optimal cytoreduction in advanced ovarian cancer treated with dose-dense paclitaxel and carboplatin followed by interval surgery at the Peruvian national institute of neoplastic diseases - Alcarraz Molina, Cindy (2018)
Objectives. To determine the rate of optimal cytoreduction in patients with advanced ovarian cancer who received neoadjuvant chemotherapy with dose-dense carboplatin and paclitaxel followed by interval debulking surgery (IDS). Materials and Methods. A retrospective study of a series of cases of Peruvian women treated with neoadjuvant chemotherapy with carboplatin (6 AUC mg/mL/min) and paclitaxel (80 mg/m2 weekly) followed by IDS, at the National Institute of Neoplastic Diseases during the 2010-2014 period. Results. The 41 patients who made it to the interval surgery had a median age of 59 years (range: 47-73 years). In 37 (90.2%) patients, high-grade serous adenocarcinoma histology was reported. Thirty-four (82.9%) achieved optimal cytoreduction and five (14.7%), a complete pathological response. Progression-free survival at one year and two years was 74.7% and 51.8%, respectively. Overall survival at one year and two years was 85.2% and 71.4%, respectively. The risk of progression and death was greater in patients without optimal cytoreduction and in patients with post-surgery levels of carcinoembryonic antigen 125 > 30 U/mL. Conclusions. Neoadjuvant therapy with dose-dense carboplatin and paclitaxel achieved an elevated frequency of optimal cytoreduction. The post-surgery levels of carcinoembryonic antigen 125 and optimal cytoreduction were independent factors of progression-free survival and overall survival.